Association between maternal stature and household-level double burden of malnutrition: findings from a comprehensive analysis of Ethiopian Demographic and Health Survey - Biniyam Sahiledengle; Lillian Mwanri; Kingsley Emwinyore Agho (BMC, 2023)
Abstract Background Undernutrition among under-five children is one of the intractable public health problems in Ethiopia. More recently, Ethiopia faced a rising problem of the double burden of malnutrition-where a mother may be overweight/obese, and a child is stated as having undernutrition (i.e., stunting, wasting, or underweight) under the same roof. The burden of double burden of malnutrition (DBM) and its association with maternal height are not yet fully understood in low-income countries including Ethiopia. The current analysis sought: (a) to determine the prevalence of double burden of malnutrition (i.e., overweight/obese mother paired with her child having one form of undernutrition) and (b) to examine the associations between the double burden of malnutrition and maternal height among mother-child pairs in Ethiopia. Methods We used population-representative cross-sectional pooled data from four rounds of the Ethiopia Demographic and Health Survey (EDHS), conducted between 2000 and 2016. In our analysis, we included children aged 0-59 months born to mothers aged 15-49 years. A total of 33,454 mother-child pairs from four waves of EDHS were included in this study. The burden of DBM was the primary outcome, while the maternal stature was the exposure of interest. Anthropometric data were collected from children and their mothers. Height-for-age (HFA), weight-for-height (WFH), and weight-for-age (WFA) z-scores < − 2 SD were calculated and classified as stunted, wasting, and underweight, respectively. The association between the double burden of malnutrition and maternal stature was examined using hierarchical multilevel modeling. Results Overall, the prevalence of the double burden of malnutrition was 1.52% (95% CI 1.39-1.65). The prevalence of overweight/obese mothers and stunted children was 1.31% (95% CI 1.19-1.44), for overweight/obese mothers and wasted children, it was 0.23% (95% CI 0.18-0.28), and for overweight/obese mothers and underweight children, it was 0.58% (95% CI 0.51-0.66). Children whose mothers had tall stature (height ≥ 155.0 cm) were more likely to be in the double burden of malnutrition dyads than children whose mothers' height ranged from 145 to 155 cm (AOR: 1.37, 95% CI 1.04-1.80). Similarly, the odds of the double burden of malnutrition was 2.98 times higher for children whose mothers had short stature (height < 145.0 cm) (AOR: 2.98, 95% CI 1.52-5.86) compared to those whose mothers had tall stature. Conclusions The overall prevalence of double burden of malnutrition among mother-child pairs in Ethiopia was less than 2%. Mothers with short stature were more likely to suffer from the double burden of malnutrition. As a result, nutrition interventions targeting households' level double burden of malnutrition should focus on mothers with short stature to address the nutritional problem of mother and their children, which also has long-term and intergenerational benefits.